The struggle for the soul of economics - Kevin D. Hoover (Duke University, Center for the History of Political Economy (CHOPE), 2021)
Macroeconomics faced substantial internal and external criticism related to the 2007-09 financial crisis. Much of it was based on the unsustainable idea that its goal could or should be unconditional forecasting of business cycles. Critics specially singled out dynamic, stochastic general-equilibrium (DSGE) models, and called for various fundamental re-orientations of the field. Predictably, the critic's proposals have not won the day. Critics exaggerated the role of DSGE models in actual policymaking, and their advocates developed the models to address some of the issues raised by the crisis. But DSGE modelers oversold its success, with some prominent advocates having argued that it is the sine qua non of successful macroeconomics. They revive an old controversy in economics between those who prioritize a priori theory and those who prioritize empirical data - a controversy classically exemplified in the Measurement without Theory Debate of the 1940s between the Cowles Commission and the National Bureau of Economic Research. That debate is reviewed for its implications for the recent controversy. In adopting the Cowles-Commission position, some DSGE modelers would essentially straight-jacket macroeconomics and undermine economic science and the pursuit of knowledge in an open-minded, yet critical framework. Some alternative approaches are noted.
Keywords: B3; B4; E1; E3; E6; 330; DSGE model; Measurement without Theory Controversy; 2007-09 financial crisis; National Bureau of Economic Research (NBER); Cowles Commission; Marshallian economics